Grammatical Processing in Schizoprenia: Analysis on Sentence Structure - Айшегюль Озджан Вурал; Гюльміра Куруоглу; Коксал Алптекін (Психолінгвістика)
Objective. Language disorder is one of the most significant symptom domains that characterizes Schizophrenia Disorder. The aim of the present study carried out considering language deviations is to investigate and compare the schizophrenic patients’ and control group’s speech in terms of sentence structure.